2022
DOI: 10.7554/elife.75893
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship of COVID-19 related stress and media consumption with schizotypy, depression, and anxiety in cross-sectional surveys repeated throughout the pandemic in Germany and the UK

Abstract: Background:Studies report a strong impact of the COVID-19 pandemic and related stressors on the mental well-being of the general population. In this paper, we investigated whether COVID-19 related concerns and social adversity affected schizotypal traits, anxiety, and depression using structural equational modelling. In mediation analyses, we furthermore explored whether these associations were mediated by healthy (sleep and physical exercise) or unhealthy behaviours (drug and alcohol consumption, excessive me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…Social support involves mutual support between individuals; consequently, individuals with secure attachments tended to perceive more social support during the COVID-19 pandemic quarantine. Furthermore, social support provides access to resources that help individuals cope with difficulties during stressful situations ( Fraley, 2019 ), ultimately improving stress responses ( Daimer et al, 2022 ; Tsuno et al, 2022 ). This style aligns with our finding that increased social support was associated with fewer mental health problems and less perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Social support involves mutual support between individuals; consequently, individuals with secure attachments tended to perceive more social support during the COVID-19 pandemic quarantine. Furthermore, social support provides access to resources that help individuals cope with difficulties during stressful situations ( Fraley, 2019 ), ultimately improving stress responses ( Daimer et al, 2022 ; Tsuno et al, 2022 ). This style aligns with our finding that increased social support was associated with fewer mental health problems and less perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…Another variable that increased the chance of being in the category of "poor mental health" was spending five or more hours online. Spending an excessive amount of time online and excessive media consumption were found to be associated to depressive and anxiety-related symptoms, and negatively associated to overall well-being [ 18 , 51 ]. The univariate logistic regressions also showed that attending university increased the possibilities of being in the category "good mental health" when compared to scientific lyceum and grammar schools, and with technical institutes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excessive media consumption during the pandemic was not covered by the intervention content and was mentioned as missing by some participants. Studies found the higher use of media during the COVID‐19 pandemic to be related to greater mental health issues (Bendau et al, 2021; Daimer et al, 2022). Therefore, dealing with media consumption could have been a helpful addition to bounce.…”
Section: Discussionmentioning
confidence: 99%